Flexural Properties of PVC/Bamboo Composites under Static and Dynamic-Thermal Conditions: Effects of Composition and Water Absorption - Shahril Anuar Bahari; Warren J. Grigsby; Andreas Krause (International Journal of Polymer Science)
Polyvinyl chloride (PVC)/bamboo composites have been prepared and assessed for their use in interior and exterior load-bearing applications. PVC composites were formed by compounding PVC with different bamboo particle sizes and loadings. The mechanical properties of these composites were determined at both ambient and elevated temperatures and after long-term water soaking. Analysis revealed that bamboo incorporation improved the PVC composite flexural modulus which was also observed with dynamic mechanical-thermal analysis on heating composites to ca. 70°C. Addition of 25% and 50% bamboo particles increases flexural modulus by 80% with dependency on whether fine (<75 μm) or coarse (<1 mm) particles were used. On water soaking to saturation, composites had water weight uptakes of 10%, with reduced flexural properties obtained for all water-soaked composites. Nonetheless, the results of this study show that PVC/bamboo composites achieve the minimum flexural performance of ASTM D 6662, indicating potential for their use in exterior applications.